2015
DOI: 10.1371/journal.pone.0135257
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cell Growth Is Differentially Affected by Constitutive Activation of NRF2 by KEAP1 Deletion and Pharmacological Activation of NRF2 by the Synthetic Triterpenoid, RTA 405

Abstract: Synthetic triterpenoids are antioxidant inflammation modulators (AIMs) that exhibit broad anticancer activity. AIMs bind to KEAP1 and inhibit its ability to promote NRF2 degradation. As a result, NRF2 increases transcription of genes that restore redox balance and reduce inflammation. AIMs inhibit tumor growth and metastasis by increasing NRF2 activity in the tumor microenvironment and by modulating the activity of oncogenic signaling pathways, including NF-κB, in tumor cells. Accumulating evidence suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 72 publications
(125 reference statements)
4
30
0
Order By: Relevance
“…Although we did not carry out in depth mechanistic studies using the G+BM combination, numerous investigators have shown the potent Hsp90 inhibitory effect of G ( 72 , 75 ) and the potent Nrf2 inductive effect of BM ( 76 , 77 ). In addition, our previous published finding documented that overexpression of Nrf2 can suppress the expression and function of AR-FL in both LNCaP and C4-2B cells ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not carry out in depth mechanistic studies using the G+BM combination, numerous investigators have shown the potent Hsp90 inhibitory effect of G ( 72 , 75 ) and the potent Nrf2 inductive effect of BM ( 76 , 77 ). In addition, our previous published finding documented that overexpression of Nrf2 can suppress the expression and function of AR-FL in both LNCaP and C4-2B cells ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent data reveal its role also as a tumor suppressor [ 32 , 33 ]. For example, Probst et al [ 34 ] found that genetic activation of Nrf2 and pharmacological activation of Nrf2 by RTA 405 are distinct, which suppress cancer cell survival and promote apoptosis. Resveratrol, the same as an antioxidant inflammation modulator, may have the same pharmacology action and mechanism and promotes the apoptosis of pancreatic cancer cells via activation of Nrf2 pathway.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that RTA 405 did not reduce the sensitivity of cancer cells towards doxorubicin and cisplatin, despite increased Nrf2 activity. Moreover, such compounds even enhanced the cytotoxicity of chemotherapeutics [ 22 ]. Similar results were also obtained for bardoxolone methyl in combination with carboplatin and paclitaxel in a mouse lung cancer model [ 23 ].…”
Section: Resultsmentioning
confidence: 99%